Inovasi lengkuas Sebagai Produk Makanan Ringan dan Tambahan Pendapatan di Desa Sukamulya - Moh. Wahyu Aminullah; Muhni Pamuji; Dina Fitria (Universitas Lancang Kuning, 2022)
This community service is carried out with the aim of optimizing the use of galangal and community empowerment in Sukamulya Village in increasing income in a sustainable manner. The method used in this activity is by direct counseling and training to the community and making galangal innovations into galangal chips. The results obtained are that the large potential of galangal must be balanced with optimal utilization by processing it first rather than selling it directly to agents. This is also supported by the enthusiasm of the community in improving welfare. The need for collaboration in terms of marketing and sales from various parties, both local governments, communities, campus parties, and other stakeholders in order to improve the community's economy, and promote healthy snacks in the midst of this COVID-19 pandemic situation. This service can indirectly increase people's knowledge in managing the potential of galangal; cultivate the mindset of collaborating to form a community that has the potential to increase people's economic income; and efforts to produce galangal chips as souvenirs from Sukamulya village.